EFEKTIVITAS SISTEM INFORMASI DALAM MENINGKATKAN KINERJA KARYAWAN SEBAGAI LAPORAN PERTANGGUNGJAWABAN - Anindita, Kristina; Puspa, Maliana; Kosnan, Wilhelmina (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
Information is an important factor for the company because it is one resource that can be processed to support business activities amid increasingly fierce competition. The role is a management information system to manage data, organizing, and retrieving information that helps organizations to provide services faster, more accurately and more easily, which affects also the performance level. Use of information systems can effectively improve the performance of employees. The research is a qualitative case study approach in Purwokerto Gramedia ELTI by conducting in-depth interviews to 6 employees. The quality of information systems and services to operationalize the system makes employees work more produktift, effective and efficient.